The rebalancing act: Injured varsity women athletes' experiences of global and sport psychological well-being. (July 2020) - Trainor, Lisa R.; Crocker, Peter R.E.; Bundon, Andrea; Ferguson, Leah
Abstract: Objectives: The purpose of this study was to explore how seriously injured women athletes perceive and experience global and sport psychological well-being (PWB) during sport injury recovery. Method: Adopting an interpretivist constructionist approach, we conducted one semi-structured interview with twelve participants (12 interviews total), aged 18–23. All participants were currently seriously injured, with a range of six months out of sport. Through a reflexive thematic analysis (Braun & Clarke, 2019) we analyzed patterns within the data related to how injured athletes perceived and experienced global and sport specific PWB during sport injury recovery. Results: Four overarching themes were developed: (1) my life is chaos and out of control, (2) pressures shaping response to sport injury, (3) maybe I can: adaptation from the disruption of sport injury, and (4) sport injury growth (SIG). Participants experienced an initial disruption of sport PWB and global PWB, however once they were able to adapt, they could rebalance their PWBs. Once rebalanced, participants reappraised the injury experience to be an opportunity for psychological growth and development, leading to the possibility of SIG. Findings suggest that sport injury can initially hinder one's PWB, however once one can rebalance their PWB sport injury is perceived as a positive event that can lead to SIG. Conclusion: These findings reveal that it is important to consider the role of PWB during sport injury, as it has been identified that there are disruptions to one's PWB. These findings help further our understanding of injured athletes' experiences of PWB during sport injury and how athletes could be better supported to protect their PWB and mental health during recovery. Highlights: At first the psychological ramifications of injury are perceived as negative. Social support was perceived only as valuable if it came from those with personal experience with injury. Adaptation was a process of reorganizing self-structure; rebalancing PWB through expansion of the self. Global PWB is viewed as the foundation to sport PWB. Reappraisal of injury as a threat to an opportunity for SIRG.